2021
DOI: 10.1002/celc.202100377
|View full text |Cite
|
Sign up to set email alerts
|

An [FeFe]‐Hydrogenase Mimic Immobilized through Simple Physiadsorption and Active for Aqueous H2 Production

Abstract: Mimicking hydrogenases with synthetic complexes is a promising strategy for the design of Earth-abundant electrocatalysts for H 2 evolution as alternative to platinum. Here, we describe a bio-inspired FeFe electrocatalyst, with a semi-bridging μ-CO ligand, active and stable for H 2 evolution in acidic aqueous solutions after its physiadsorption onto carbon-based electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…116 H 2 production was confirmed by RRDE, bulk electrolysis experiments demonstrated a Faradaic efficiency of ∼89 ± 3%, and the turnover number (TON) and turnover frequency (TOF) were determined to be TON = 4.9 ± 0.1 × 10 5 , TOF = 15.3 ± 0.3 s −1 . 116 The electrochemical data of heterogeneous HER catalyzed by the above complexes are summarized in Table 1.…”
Section: ■ Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…116 H 2 production was confirmed by RRDE, bulk electrolysis experiments demonstrated a Faradaic efficiency of ∼89 ± 3%, and the turnover number (TON) and turnover frequency (TOF) were determined to be TON = 4.9 ± 0.1 × 10 5 , TOF = 15.3 ± 0.3 s −1 . 116 The electrochemical data of heterogeneous HER catalyzed by the above complexes are summarized in Table 1.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Complex J (Figure 11) is a FeFe-analogue of complex I (Figure 11) and is an efficient and robust HER electrocatalyst in acidic water. 116 Complex J (Figure 11) is a rare example of a [FeFe]-hydrogenase synthetic model containing a semibridg-ing CO, as observed in the active site of [FeFe]-hydrogenase enzyme systems. 50 However, reduction of these complexes in homogeneous solution results in disproportionation of this complex and loss of the bridging CO. 116 These bimolecular processes are naturally inhibited when adsorbed on electrodes, clearly demonstrating the advantage of heterogenization, allowing investigation of HER by μCO-bridged FeFe complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these complexes display catalytic redox oxidation states relevant to those of the hydrogenases. Besides, they have been shown to display HER activity in acidic aqueous solutions after their physical adsorption onto carbon-based electrodes , ([4] + : TON = 4.9(0.1) × 10 5 in 9 h, TOF = 15.3(0.3) s –1 , at −0.80 V vs SHE, pH 4; [5] + : TON = 7.2 × 10 6 in 10 h, TOF = 200 s –1 , at −0.85 V vs SHE, pH 3).…”
Section: Strategies For Optimized Electron Transfersmentioning
confidence: 99%
“…Recently, we described the H 2 production reactivity of two dinuclear M II Fe II (M = Fe or Ni) complexes with similar structures. We have demonstrated that both [(L N2S2 )Ni II Fe II Cp(CO)] + ( Ni II Fe II ) 9,10 and [(L N2S2 )(MeCN)Fe II (CO)Fe II Cp] + ( Fe II Fe II ) 11,12 complexes (L N2S2 : 2,2′-(2,2′-bipyridine-6,6′-diyl)bis(1,1′-diphenylethanethiolate), Cp = cyclopentadienyl, Scheme 1) display comparable electrocatalytic performance for H 2 production, both following an E [ECEC] catalytic mechanism (E = electron transfer, C = chemical reaction, e.g. , a protonation step in the present case).…”
Section: Introductionmentioning
confidence: 99%